KOMPOSISI DAN TEKNIK PERMAINAN ALAT MUSIK MARAWIS PADA LAGU â€œSUFNA YUNAâ€ DI PONDOK AL-MUAWWANAHYUNA DI PONDOK AL-MUAWWANAH - Efrianti, Baiq Ririn Ety (Universitas Hamzanwadi, 2019)
This study aimed to describe the composition and technique of Marawis musical instrument play on the song ?Sufna Yuna? in Pondok Al-Muawwanah, Johar Baru, Penujak Village, Central Lombok Regency. The research was conducted in Johar Baru, Penujak Village. The approach used in this study was descriptive qualitative. The object of this research was the marawis music of Al-Muawwanah boarding school which includes the composition and technique of playing musical instruments marawis on yuna sufna songs. Data collections were done by 1) observation, 2) interviews, and 3) documentation. Data analysis was carried out by 1) data reduction, 2) data presentation, and 3) conclusions. To check the validity of the data, the data validity technique is Credibility. From the results of the study found about: 1) the composition of musical instruments marawis on yuna sufna songs include rhythm / rhythm, tempo, dynamics, poetry, and instruments. 2) the technique of playing musical instruments marawis on yuna Sufna songs consists of the technique of playing or technique, and the sound of each musical instrument.